2021
DOI: 10.2174/1570163817666200827111127
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Chemical Composition, Antioxidant Property, and In-vitro Anticancer Activity of Silymarin from Silybum marianum on Kb and A549 Cell Lines

Abstract: Introduction: This study aimed to evaluate the antioxidant property of silymarin (SM) extracted from the seed of Silybum marianum and its anticancer activity on KB and A549 cell lines following 24, 48, and 72 h of treatment. Methods: Ten grams of powdered S. marianum seeds were defatted using n-hexane for 6 hours and then extracted by methanol. The silymarin extracted of extraction components The extracted components of silymarin were measured by spectrophotometric assay and HPLC analysis. 2, 2-diphenyl-1-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Silybin and silymarin have been used for centuries as natural remedies for hepatitis and cirrhosis [6][7][8][9][10][11][12][13]. Recent reports have demonstrated that silybin also has anti-inflammatory [14] and anti-proliferative [15] effects, antioxidant properties [16], anti-tumor [17], anti-cancer activities [18][19][20][21], and insulin-sensitizing properties [22,23]. Silybin B exhibits anti-tumor activity, is the most effective anti-fibrillogenic and anti-oligomeric component of silymarin against Aβ amyloid growth, and is a promis- ing anti-Alzheimer drug candidate [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Silybin and silymarin have been used for centuries as natural remedies for hepatitis and cirrhosis [6][7][8][9][10][11][12][13]. Recent reports have demonstrated that silybin also has anti-inflammatory [14] and anti-proliferative [15] effects, antioxidant properties [16], anti-tumor [17], anti-cancer activities [18][19][20][21], and insulin-sensitizing properties [22,23]. Silybin B exhibits anti-tumor activity, is the most effective anti-fibrillogenic and anti-oligomeric component of silymarin against Aβ amyloid growth, and is a promis- ing anti-Alzheimer drug candidate [24,25].…”
Section: Introductionmentioning
confidence: 99%